Role of Gender in Morbidity and Mortality of Extremely Premature Neonates - Binet, Marie-Eve; Bujold, Emmanuel; Lefebvre, Francine; Tremblay, Yves; Piedboeuf, Bruno; null (American Journal of Perinatology, 2012)
We investigated the effect of gender on survival and short-term outcomes of extremely premature infants (≤27 weeks) born in Canada. The records of infants admitted between 2000 and 2005 to a neonatal intensive care unit participating in the Canadian Neonatal Network were reviewed for infant gender, birth weight, gestational age, outborn status, Score for Neonatal Acute Physiology II, and antenatal corticosteroid exposure. The following outcomes were recorded: survival at final discharge, necrotizing enterocolitis, bronchopulmonary dysplasia (BPD), intraventricular hemorrhage grade ≥3, retinopathy grade ≥3, days on ventilation, and length of hospital stay. Among 2744 extremely premature infants, 1480 (54%) were male and 1264 (46%) were female. Mean birth weight of female neonates was significantly lower at each week of gestational age. Although no significant difference in survival at discharge was found between genders overall, the prevalence of BPD, combined adverse outcomes, and mortality for infants born between 24 and 26 weeks were significantly higher in males. This study suggests that, in the postsurfactant era, males remain at higher risk of respiratory complications and may have higher mortality when born between 24 and 26 weeks of gestation.
Keywords: prematurity; gender; birth; necrotizing enterocolitis; retinopathy of prematurity; intraventricular hemorrhage; bronchopulmonary dysplasia; NICU; death